Mindfulness-Based Versus Story Reading Intervention in Public Elementary Schools: Effects on Executive Functions and Emotional Health - Milaré, Claudete A. R.; Kozasa, Elisa H.; Lacerda, Shirley; Barrichello, Carla; Tobo, Patricia R.; Horta, Ana Lucia D. (Frontiers in Psychology, 2021)
In this study we compared the effects of a Mindfulness-Based Intervention (MBI) with a Story reading Intervention (SI) on the executive functions and psychological profile of children in two different public schools in São Paulo, Brazil. Methods: In this controlled clinical trial, 207 8-9-year-olds answered the Five Digit Test (FDT), which evaluates levels of stress, depression, anxiety, positive and negative affect and executive functions, at baseline (T0) and eight weeks later (T1). From T0 to T1, School 1 participated in MBI classes and School 2 in SI classes. Results: In School 1 (MBI), children improved their scores on all tests except Reading (errors) and Counting (errors) compared with School 2. No differences were observed between groups in terms of emotional health. Conclusion: It is feasible to implement MBI or SI in Brazilian public schools. Students in the MBI group presented broader effects in executive functions, while students in the SI group showed a trend towards reduced negative affect and depression symptoms.